PENINGKATAN PASSING BAWAH BOLA VOLI DENGAN MODIFIKASI BOLA KERTAS DI SDN 35 SEKIBUL - Iter, Purwanti; Haetami, Mimi; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:Problems in this research is there an increase in learning outcomes passing down the volley ball with the modification of the ball of paper on students of class IV SDN 35 Sekibul. The purpose of this study is to determine the increase of passing under the volley ball with the modification of the ball on the students of grade IV SDN 35 Sekibul. This research is a class action research with the subject of fourth grade students of SDN 35 Sekibul totaling 20 students. The results of the first cycle of students who completed 12 or 60% while the students and who have not passed or not yet completed is still the same amounted to 8 or 40% then proceed to cycle II students in order to have the opportunity for improvement so can be categorized graduate or complete all with students graduated amounted to 20 students and has not completed 0 or none.Â Keywords: Passing, Modification of the ball